A high-throughput screening of metal–organic framework based membranes for biogas upgrading. (13th September 2021) - Glover, Joseph; Besley, Elena
Abstract : High-throughput computational screening methodology designed to identify the most promising porous metal–organic frameworks for biogas upgrading. Abstract : Applications of biomethane as a source of renewable energy and transport fuel rely heavily on successful implementation of purification methods capable of removing undesirable impurities from biogas and increasing its calorific content. Metal–organic frameworks (MOFs) are competitive candidates for biogas upgrading due to a versatile range of attractive physical and chemical properties which can be utilised in membrane materials. In this work, we present a high-throughput computational screening methodology for efficient identification of MOF structures with promising gas separation performance. The proposed screening strategy is based on initial structural analysis and predictions of the single-component permeation of CO2, CH4 and H2 S from adsorption and diffusion calculations at infinite dilution. The identified top performing candidates are subject to further analysis of their gas separation performance at the operating conditions of 10 bar and 298 K, using grand canonical Monte Carlo and equilibrium molecular dynamics simulations on equimolar CO2 /CH4 and H2 S/CH4 mixtures. The Henry constant for the adsorption of H2 O was also calculated to determine the hydrophobicity of MOF structures, as the presence of H2 O often leads to membrane instability and performance limitations. For the considered gas mixtures, the top MOF candidates exhibit superior separation capabilities over polymer-, zeolite-, and mixed matrix-based membranes as indicated by the predicted values of selectivity and permeability. The proposed screening protocol offers a powerful tool for the rational design of novel MOFs for biogas upgrading.